Instruments for conducting comprehensive interviews with victims and informants of sexual harassment in the university environment - Saeteros Hernández, Rosa C.; Maldonado Montoya, Gabriela B.; Mejía Paredes, Martha C.; Zayas, Eida O. (International Journal of Research in Medical Sciences, 2025)
Background: Having qualitative research instruments to study sexual harassment at university is essential to understand the experiences and perceptions of victims, improving the quality of research and interventions to prevent and address this problem. Objective was to validate, by experts, in-depth interview instruments for victims of sexual harassment and key informants in the university environment. Methods: In-depth interview instruments for victims and key informants of sexual harassment allow to investigate qualitative data on sexual harassment at the university, such as: perceptions, the context in which it occurs, experiences of sexual harassment, perceived needs, physical, psychological, social and academic effects, as well as the perception of individual and institutional actions against sexual harassment. Results: In-depth interview instruments for victims and key informants of sexual harassment allow to investigate qualitative data on sexual harassment at the university, such as: perceptions, the context in which it occurs, experiences of sexual harassment, perceived needs, physical, psychological, social and academic effects, as well as the perception of individual and institutional actions against sexual harassment. Conclusions: In-depth interviews with victims of university sexual harassment and key informants allow to obtain relevant data from the students' perspective, pertinent information to identify the complexity of university sexual harassment and to commit the university to the implementation of effective prevention, intervention and comprehensive reparation policies.